Justifying America's Wars : the Conduct and Practice of US Military Intervention. - Kerton-Johnson, Nicholas (Contemporary Security Studies, 2010)
Focuses on the justifications for, and practice of, war by the US since 1990, and examines four case studies: the Gulf War, Kosovo, Afghanistan and Iraq. The author undertakes an examination of presidential speeches and public documents from this period to determine the focal points on which the respective presidents based their rhetoric for war.